The sensation of security: private guards and social order in Brazil - Robb Larkins, Erika (Police/Worlds: Studies in Security, Crime, and Governance, 2023)
The Sensation of Security explores how private security guards are a permanent, conspicuous fixture of everyday life in the Brazilian city of Rio de Janeiro. Drawing on long term ethnographic research with security laborers, managers, company owners, and elite global consultants, Erika Robb Larkins examines the provision of security in Rio from the perspective of security personnel, providing an analysis of the racialized logics that underpin the ongoing work of securing the city. Larkins shows how guards communicate a sensação de segurança (a sensation of security) to clients and customers who have the capital to pay for it. Cultivated through performances by security laborers, the sensation of security is a set of culturally shaped racialized and gendered impressions related to safety, order, well-being, and cleanliness. While the sensação de segurança indexes an outward facing task of allaying fear of crime and maintaining order in elite spaces, it also refers to the emotional labor and embodied worlds that security workers navigate.